STUDY ON PHYSICAL AND SENSORICAL CHARACTERISTICS OF FLESH RESTRUCTURED WITH SAGO CATFISH JERKY - Amir Jayani; Zulman Efendi; Devi Silsia (Jurnal Agroindustri, 2014)
This study aims to gain influence the thickness and concentration variations affect the characteristics of sago binder physical properties of catfish jerky. As well as getting influence the thickness and concentration variations affect the level of binder sago joy panelists in terms of organoleptic test. Data were analyzed by analysis of variance using the Analysis Of Variance (ANOVA). If there is a significant difference followed by a further test of DMRT 5% level (physical properties). While the hedonic test performed using Kruskal Wallis analysis. Results uniformity analysis (ANOVA) showed catfish fillet thickness and concentration of sago affect the physical properties of the water content and the level of violence. Where catfish jerky using sago binder 5% and 10% significantly different. The use of sago binder 5% and 10% led to an increase in water content. Besides the addition of the binder resulted in increasing levels of violence catfish jerky. Based on the statistics found that the influence of the thickness and concentration of the binder sago aroma, flavor and color of the sixth jerky catfish were not significantly different. But the texture was significantly different.